Bibliometric Analysis of Renewable Energy Use in Low Carbon Development - PRASETYADEWI, Venita; NURMANDI, Achmad; FRIDAYANI, Helen Dian; ATMOJO, Muhammad Eko (International Journal of Environmental, Sustainability, and Social Science, 2024)
Greenhouse gases are gases trapped in the earth's atmosphere that cause the earth's surface temperature to become hot, when during the day the sun emits rays that can penetrate into the earth's atmosphere and warm the earth while at night the earth's surface becomes cold and can release the earth's heat back into the air, with the presence of these gases so that they can reflect the earth's heat back to the earth again because that is called greenhouse gases. Greenhouse gases that occur due to excessive human activity resulting in the release of a number of greenhouse gases into the earth's atmosphere. Greenhouse gases are caused by excessive human activity that results in the release of a number of greenhouse gases into the earth's atmosphere. Greenhouse gases increased in 2020 due to factors such as the burning of coal, oil and natural gas produced from Indonesia's industrial energy sector. Then there was a decrease in gas emissions, due to Covid-19 in the use of fuel in the transportation sector, but in 2021 until now there has been an increase caused by the energy sector and industrial activities. Based on this, this analysis focuses on government efforts to reduce greenhouse gases. In this analysis, using bibliometric analysis as a method used to analyse how trends and developments regarding research on greenhouse gases. The results of this analysis refer the government's real steps by using renewable energy such as solar energy and geothermal energy to reduce the effects of greenhouse gases.